A technology review : Newcastle disease, with special emphasis on its effect on village chickens - Alexander, Dennis J.; Bell, Jonathan G.; Alders, R. G. (Rome : Food and Agriculture Organization of the United Nations, 2004)
Keeping poultry makes a substantial contribution to household food security throughout the developing world. One of the principal constraints to increasing small-scale poultry production is Newcastle Disease. This acute viral disease can typically kill up to 80 percent of unprotected poultry in rural areas and is found throughout the developing world. This technology review presents the latest understanding of Newcastle Disease, its characteristics, epidemiology, symptoms and control.
Keywords: Newcastle disease -- Control; Chickens -- Diseases -- Control; Newcastle disease vaccine